FABEL BANJAR SEBAGAI MEDIA PENDIDIKAN KARAKTER - Yulianto Agus (Balai Bahasa Sulawesi Tengah, 2016)
The aim of this study is to find out the quality of character building in Banjarfable. This study presententing a problem about is there positive quality ofcharacter building in Banjar fable for the readers. This study uses descriptivemethod and library research. Base on the study it can be found that Banjar fablehas positive quality of character building so it can be said that Banjar fable canbe used as one of media resource to build positive character for the readers.